High spatio‐temporal resolution measurements of cohesive sediment erosion. Issue 11 (14th June 2020) - Beckers, Felix; Inskeep, Caleb; Haun, Stefan; Schmid, Gerhard; Wieprecht, Silke; Noack, Markus
Abstract: In this study, we present a novel approach to measure fundamental processes of cohesive sediment erosion. The experimental setup consists of a laboratory erosion flume (SETEG) and a photogrammetric method to detect sediment erosion (PHOTOSED). Detailed data are presented for three erosion experiments, which were conducted with a natural non‐cohesive/cohesive sediment mixture at increasing sediment depths (4, 8, 16 cm). In each experiment, the sediment was exposed to a set of incrementally increasing shear stresses and the erosion was measured dynamically, pixel‐based, and approximate to the process scale given the resolution of PHOTOSED. This enables us to distinguish between (i) individual emerging erosion spots caused by surface erosion and (ii) large holes torn open by detached aggregate chunks. Moreover, interrelated processes were observed, such as (iii) propagation of the erosion in the longitudinal and lateral direction leading to merging of disconnected erosion areas and (iv) progressive vertical erosion of already affected areas. By complementing the (bulk) erosion volume profiles with additional quantitative variables, which contain spatial information (erosion area, specific deepening, number of disconnected erosion areas), conclusions on the erosion behaviour (and the dominant processes) can be drawn without requiring qualitative information (such as visual observations). In addition, we provide figures indicating the spatio‐temporal erosion variability and the (bulk) erosion rates for selected time periods. We evaluate the variability by statistical quantities and show that significant erosion is mainly confined to only a few events during temporal progression, but then considerably exceeds the time‐averaged median of the erosion (factors between 7.0 and 16.0). Further, we point to uncertainties in using (bulk) erosion rates to assess cohesive sediment erosion and particularly the underlying processes. As a whole, the results emphasise the need to measure cohesive sediment erosion with high spatio‐temporal resolution to obtain reliable and robust information. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : The highly dynamic erosion progress is investigated for three experiments, which were conducted with a natural non‐cohesive/cohesive sediment mixture, using a photogrammetric method to detect sediment erosion (PHOTOSED). Given the high spatio‐temporal resolution of the measurements, fundamental and interrelated erosion processes are identified and the spatio‐temporal erosion variability over the surface is evaluated.